Manajemen Pembelajaran Berbasis Karakter dalam Pembentukan Akhlak Siswa pada SMA Negeri 5 Lhokseumawe - Tasnim, Yusrizal, Khairuddin. (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2016)
Character-based learning management can be implemented by determining students’ ability and character in order to achieve quality learning outcomes. This research aimed to find out the planning, implementation, and assessment of character-based learning program in building students’ moral of State Senor High School 5 of Lhoseumawe. Research approach used was descriptive qualitative. Techniques of collecting sample used were interview, observation, and documentation. Research subjects were principal, science teachers, and students in State Senior High School 5 of Lhokseumawe. The result showed that: 1) The subject teacher at State Senior High School 5 of Lhokseumawe has made program planning of character-based learning including syllabi and lesson plan documented in learning administration containing greetings pronunciation program, inland program material to students by knowing the characteristics of the students, as well as programs to educate, guide and train students to be responsible and tolerant attitude toward others. 2) The implementation of character-based learning program has been implemented by the subject teacher in the learning process as greeting at the beginning and at the end of the lesson, well behaved and not rude to students, encourage students to always love to God, creating a conducive learning environment, giving the interior of the material to determine the characteristics of the students, as well as educate, train and mentor students to have a sense of responsibility and tolerance towards others Implementation of the character-based learning programs were also carried out by the school through regular activities and extracurricular activities held in SMAN 5 Lhokseumawe. 3) The assessment of character-based learning program has been implemented according to applicable curriculum through pre-test, assignments, post-test, and assessment of students’ behaviour through is the student's personal record sheet observation, interview, and portfolios.